I wonder why penguins can't fly - "Jacobs, Pat" (Kingfisher London, 2011)
"I Wonder Penguins Can't Fly" takes a look at the coldest places on Earth - the Poles. Readers will learn about animals that live at the Poles, such as polar bears, penguins and seals; and also discover how plants survive at the Poles, why the polar ice caps are in danger of melting, and how scientists gather important information about the climate and more in these harsh environments. (publisher)